Dynamic Curvature Steering Control for Autonomous Vehicle: Performance Analysis - Muhammad Aizzat, Zakaria; Hairi, Zamzuri; Saiful Amri, Mazlan (IOP Publishing, 2016)
This paper discusses the design of dynamic curvature steering control for autonomous vehicle. The lateral control and longitudinal control are discussed in this paper. The controller is designed based on the dynamic curvature calculation to estimate the path condition and modify the vehicle speed and steering wheel angle accordingly. In this paper, the simulation results are presented to show the capability of the controller to track the reference path. The controller is able to predict the path and modify the vehicle speed to suit the path condition. The effectiveness of the controller is shown in this paper whereby identical performance is achieved with the benchmark but with extra curvature adaptation capabilites.